Sexual Dimorphism of Growth Hormone in the Hypothalamus: Regulation by Estradiol - Addison, Melisande L. (Endocrine Society, 2012)
GH is best known as an anterior pituitary hormone fundamental in regulating growth, differentiation, and metabolism. GH peptide and mRNA are also present in brain, in which their functions are less well known. Here we describe the distribution of GH neurons and fibers and sex differences in Gh mRNA in adult mouse brain. Cell bodies exhibiting GH immunoreactivity are distributed in many brain regions, particularly in the hypothalamus in which retrograde labeling suggests that some of these cells project to the median eminence. To determine whether Gh mRNA is sexual dimorphic, we carried out quantitative RT-PCR on microdissected brain nuclei. Ovary-intact mice had elevated Gh mRNA in the arcuate nucleus and medial preoptic area (MPOA) compared with gonad-intact males. In males, castration increased Gh mRNA in the MPOA, whereas ovariectomy decreased Gh mRNA in both regions. When gonadectomized adults of both sexes were treated with estradiol Gh mRNA increased in females but had no effect in castrated males. Tamoxifen was able to blunt the rise in Gh mRNA in response to estradiol in females. In addition, we found that estrogen receptor-α is coexpressed in GH neurons in the MPOA and arcuate nucleus. In summary, the findings reveal sexual dimorphisms in Gh gene expression in areas of the brain associated with reproduction and behavior. Interestingly, estradiol enhances Gh mRNA in females only, suggesting that multiple factors orchestrate this sexual dimorphism.